Macrophotography of Moths as an Educational Tool to Promote Tourism and Culture in the Parish of Chonta Punta, Napo, Ecuador for Older People - Quezada-Sarmiento, Pablo Alejandro; Xavier Andres Barnuevo-Solís; Patricia Marisol Chango-Cañaveral; Wilson Teodomiro Salas-Alvarez; Alfonso David Jiménez-Arias (My University, 2025)
Macrophotography is proving to be an educational tool for capturing details of the objects photographed, particularly to reveal the amazing variety of colors and shapes that characterize moths. In this sense, it is a tool that can well promote entomotourism in the community of Chonta Punta, located in the province of Napo—Ecuador for older people. Moth activity was documented during 17 nightly monitoring sessions at three randomly selected locations in the Yachana Foundation, Agua Santa. 4497 images were taken, and 395 species were identified. The usefulness of macrophotography in revealing useful information about insects was documented and supported by a systematic literature review. The literature review revealed that primary forests harbor moth species absent from eucalyptus plantations. Reporting on these insects demonstrates their potential as attractions within entomotourism, as well as their role as indicators of forest health. The country has untapped potential to turn moth diversity into a tourist attraction. Examples such as the butterfly farms in Mindo, just 2 h from Quito, are clear evidence of the interest butterflies generate among visitors. In addition, experiences such as visiting bioluminescent worms in New Zealand present insects as an attraction. In the context of this research, macrophotography is positioned as an indispensable tool for the identification of insects, allowing a detailed study of their morphology and unique characteristics, as a basis for the development of cultural and tourist proposals around these insects.
Keywords: Details; Entomotourism-ism; Insects; Photography; Taxonomy; TIC first section